Influence of parental socio-economic factors on the delinquent behaviour among secondary school students in Ibadan, Oyo state (2020)
This study investigated the influence of parental socio-economic factors on the delinquent behaviour among secondary school students in Ibadan North Local Government Area of Ovo Slate. The study adopted the descriptive survey research design while Social Learning Theory was adopted as a theoretical guide Two hundred secondary school students were selected for the study using simple random sampling technique The research instruments used to collect data were the Parental education scale with a Cronbach alpha reliability of 0.82; Parental income has a Cronbach alpha reliability off). 79; while Parental occupation has a Cronbach alpha reliability of 0.84 and Delinquent behaviour has a Cronbach alpha reliability of 0.89. The data collected were analysed, using Pearson's Product Moment Correlation at 0.05 level of significance. The findings revealed that there was a positive significant relationship between parental education and delinquent behaviour (r= .426, p < 0.05). There was a significant relationship between parental income and delinquent behaviour (r- .365, p < 0.05). There was significant relationship between parental occupation and delinquent behaviour (r =.429** p < 0.05). The study concluded that the financial strength of a family could trigger delinquent behaviour among students. Consequently, it was recommended that parents and caregivers should endeavour to meet the needs of their children and wards as this would make them not to engage in delinquent behaviours.